Dynamics of excited-state conformational relaxation and electronic delocalization in conjugated porphyrin oligomers. - Chang, M; Hoffmann, M; Anderson, H; Herz, L (2008)
We have investigated the influence of nuclear geometric relaxation on the extent of the excited-state electronic delocalization in conjugated zinc porphyrin oligomers using ultrafast transient photoluminescence spectroscopy. By use of metal-coordinating templates that force the oligomers into specific geometries in solution we are able to distinguish clearly between relaxation effects arising from the two vibrational modes that preferentially couple to the electronic transitions in such materials, i.e., carbon-carbon bond stretches and inter-ring torsions. We find that light absorption generates an excited state that is initially strongly delocalized along the oligomer but contracts rapidly following vibrational relaxation of the nuclei along C-C stretch coordinates on the subpicosecond time scale. We are able to monitor such excitonic self-trapping effects by observing the extent to which the concomitant ultrafast rotation of the transition dipole moment is found to correlate with the degree of bending induced in the molecular backbone. We further demonstrate that interporphyrin torsional relaxation leads to a subsequent increase in the excited-state electronic delocalization on a longer time scale (approximately 100 ps). Such dynamic planarization of the molecular backbone is evident from the time-dependent increase in the overall emission intensity and red-shift in the peak emission energy that can be observed for wormlike flexible porphyrin octamers but not for torsionally rigidified cyclic or double-strand octamer complexes. These results therefore indicate that, following excitation, the initially highly delocalized excited-state wave function first contracts and then expands again along the conjugated backbone in accordance with the time periods for the vibrational modes coupled to the electronic transition.